PROCESS DIMENSION ANALYSIS ON THE SUCCESS OF CHILD MARRIAGE PREVENTION POLICY - AHMAD YUSRONI; Khairur Raziqin; Muhammad Dzul Fadli (Jurnal Ilmiah Wahana Bhakti Praja, 2025)
Children are the foundation of a nation's human resources, an important issue affecting child welfare is child marriage. The East Java Provincial Government issued a policy in the form of a Governor's Circular Letter (SE) on the prevention of child marriage, Malang Regency as an area with a high marriage rate in East Java followed up on the SE. After three years, the efforts made have succeeded in reducing the number of child marriages in Malang District each year. This article analyzes the follow-up process of the child marriage prevention policy in Malang District using a descriptive qualitative research method, case study research type with Allan McConnell's Policy Success theory as the analytical knife. This article explores the success of the child marriage prevention policy from the process dimension, as well as the level of success using the degree of policy success/failure. The results showed the success of the policy in the process dimension, firstly maintaining policy objectives / instruments, all SE Child Marriage Prevention objectives were maintained with several derivative policies, although there was one policy instrument related to the budget that was not fully maintained. The level of success is included in Resilient Success. Second, ensuring policy legitimacy, where the entire SE follow-up process is legitimized by all parties, so the success level is included in Success. Third, building a sustainable coalition, the Malang District Government built a sustainable coalition to overcome the problem of child marriage through the policies made. The success rate is also included in Success.